2005
DOI: 10.1111/j.1365-2257.2005.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese collaborative study for fibrinogen assay: variability of the fibrinogen assay between different laboratories does not improve when a common calibrator is used

Abstract: Several national and local external quality assurance schemes have been developed to improve the plasma fibrinogen assay in Japan over the past 30 years. Now most commercial calibrant plasma may be calibrated against an International Standard preparation, in order to achieve agreement of results obtained by different laboratories. However, we have never achieved satisfactory results, according to an external quality control survey regarding the fibrinogen assay. Therefore, we distributed two kinds of fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…3240 Recently, Fenger-Eriksen and colleagues 41 showed that the results of Clauss measurement differ significantly in the presence of colloid plasma expander when using different automated coagulation analysers. Variability can also be introduced by different commercially available calibrators, 42 or by heterogeneity of fibrinogen (high molecular weight fraction/low molecular weight fraction) in different patient groups compared with the calibration material. 4344 Each of these factors alone might not be clinically relevant in the perioperative setting, but taken together they could invalidate comparisons between studies.…”
Section: Discussionmentioning
confidence: 99%
“…3240 Recently, Fenger-Eriksen and colleagues 41 showed that the results of Clauss measurement differ significantly in the presence of colloid plasma expander when using different automated coagulation analysers. Variability can also be introduced by different commercially available calibrators, 42 or by heterogeneity of fibrinogen (high molecular weight fraction/low molecular weight fraction) in different patient groups compared with the calibration material. 4344 Each of these factors alone might not be clinically relevant in the perioperative setting, but taken together they could invalidate comparisons between studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many sources of variability in measuring fibrinogen concentration-type of readout, reagent or activator, calibrator, and device-which affect both intra-and interlaboratory consistency. 26 One option for reducing interlaboratory variation is to use a common calibrator, 12,27,28 but it has been suggested that variability would persist even with a common calibrator and an automatic coagulometer. 28 In our study, fibrinogen concentration in patients undergoing cardiovascular surgery was measured using three types of Clauss reagent.…”
Section: Discussionmentioning
confidence: 99%
“…26 One option for reducing interlaboratory variation is to use a common calibrator, 12,27,28 but it has been suggested that variability would persist even with a common calibrator and an automatic coagulometer. 28 In our study, fibrinogen concentration in patients undergoing cardiovascular surgery was measured using three types of Clauss reagent. One type was used for the mechanical methods (steel ball and hook coagulometers) and two others were used for the electromechanical method (automated STA-R coagulometer) and the photooptical method (CA-7000 coagulometer).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown considerable interlaboratory variations in plasma fibrinogen assay results. Several attempts have been made to improve interlaboratory variation in fibrinogen measurements (Chantarangkul, Tripodi & Mannucci, 1994; Takamiya et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%